1993
DOI: 10.1530/jrf.0.0970065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dilution procedure and culture conditions after thawing on survival of frozen bovine blastocysts produced in vitro

Abstract: Blastocysts derived from bovine zygotes fertilized and matured in vitro and cultured for 7 days in conditioned medium were frozen in 1.36 mol glycerol l-1 and 0.25 mol sucrose l-1. In vitro survival after thawing was unaffected by dilution rate in 0.25 mol sucrose l-1. The proportion of blastocysts that re-expanded after 24 h was 81% (70 of 86) and 47% (33 of 70) hatched. Seven pregnancies beyond 2 months resulted from transfer of 21 blastocysts to 19 recipients. Total embryonic loss was 46.2%, of which 31% oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 4 publications
1
15
0
2
Order By: Relevance
“…In the second experiment, delipidated, sham and control Day-7 blastocysts were frozen using a conventional slow freezing procedure (19). This protocol is used for in vivo-produced embryos and is not optimal for in vitro ones, but the purpose of this freezing thawing process was to submit the different groups of IVP embryos to the same extreme conditions during the freezing process, and to make the differences between the groups more evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second experiment, delipidated, sham and control Day-7 blastocysts were frozen using a conventional slow freezing procedure (19). This protocol is used for in vivo-produced embryos and is not optimal for in vitro ones, but the purpose of this freezing thawing process was to submit the different groups of IVP embryos to the same extreme conditions during the freezing process, and to make the differences between the groups more evident.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro-produced Day 7 blastocysts were frozen according to the protocol of Massip et al (1993), used for in vivo-produced embryos. Our purpose was to submit the different groups of IVP embryos to the same extreme conditions during the freezing process, and to make the differences among the groups more evident.…”
Section: Freezing Proceduresmentioning
confidence: 99%
“…Massip et al (1993a). After thawing (15 s in a 20°C water bath), the contents of each straw was expelled into a petri dish and mixed by shaking rapidly; after 10 min at room temperature, embryos were washed twice in PBS for 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the percentage of hatched embryos can be further improved by modifying postthaw culture conditions. Massip et al (1993) found hatching rates for frozen/thawed, in vitro-produced embryos were 41% when culture was performed in the presence of bovine oviductal epithelial cells, whereas hatching rate using other culture conditions not involving coculture was 0-6%. Nonetheless, one would not expect optimal pregnancy rates to be achieved following direct transfer of embryos frozen in glycerol even with the inclusion of cytochalasin B treatment.…”
Section: Discussionmentioning
confidence: 97%